ANALISA KEGAGALAN FATIK PADA PLUNGER POMPA TORAK RECIPROCATING 5H3S - Yose Rizal; Sepfitrah - (Universitas Pasir Pengaraian, 2014)
Pumps supply water used for steam generators in PT. CPI is a reciprocating type IR 5H3S used in the steam generators to be processed in order to supply water to steam. Compression pressure reciprocating pump is very large reaching 89.6 bars, is used to push the volume of liquid to be transferred through the exhaust system. The pressure generated by the movement of the pump plunger working pump suction and presses to compress the fluid. In fact plunger has fail until crack at the operational pressure.This study was conducted with the procedure properly. Through several stages with both the identification and investing the incident, which includes mechanical test hardness test, photo documentation fraktografi (mikrofraktografi and makrofraktografi) the material shaft patah. As approach to the truth has simulation to see the distribution of the forces acting on the piston rod (plunger rod).